LIFESTYLE, PERCEIVED VALUE DAN CUSTOMER VALUE PADA MINAT BELI - Nurdin, Sahidillah; Sulastri, Astri (Politeknik Negeri Bandung, 2018)
This research is motivated by the rapid growth of upper middle class society, increasingly sophisticated era, and increasingly modern lifestyles, demands for fast paced to make people want a simple residence, strategic, complete facilities, suitable price, comfortable and safe. The purpose of this research is to know the description and influence Lifestyle, Perceived Value, and Customer Value to Buy Interest at Dago Suites Apartment Bandung. The method used is descriptive quantitative and verifikatif. Questionnaires were distributed to 100 respondents using incidental sampling method. The results show lifestyle, perceived value and customer value can establish well and positive buying interest community.Â Keywords: Lifestyle, Perceived Value, Customer Value, Buying interest.